Problems Dispute Financing Problems in Islamic Banks from the Perspective of Islamic Law and Economics ( Case Study: Decision Number 1352/ Rev.G /2024/ PA.Trk ) - Ria Regita; Mutia Izzatun Nurul Imamah; Rohmawati; Kutbuddin Aibak (JURNAL ILMU SYARIAH, 2025)
Problematic financing is one of the main challenges faced by Islamic banks, as it directly affects financial stability, customer trust, and compliance with Sharia principles. Disputes arising from problematic financing require not only legal certainty but also substantive justice grounded in Islamic economic values. This study aimed to analyze disputes arising from problematic financing in Islamic banks from the perspectives of sharia law and Islamic economics, using Decision Number 1352/Pdt.G/2024/PA.Trk as a case study. The research used a normative legal method with a case study approach by analyzing court decisions, laws and regulations, and literature on sharia law and Islamic economics. The results showed that the settlement of problematic financing disputes in this decision referred to formal aspects of positive law and basic principles of sharia contracts, but did not fully reflect the principles of justice, public benefit, and risk sharing as emphasized in fiqh muamalah and maqāṣid al-sharī‘ah. From the perspective of Islamic economics, the applied dispute-resolution mechanism had the potential to create an imbalance between the bank's and the customer's interests. This study highlighted the importance of a more comprehensive integration of positive law, sharia principles, and Islamic economic considerations to resolve problematic financing disputes in Islamic banking. Keywords: Problematic Financing; Islamic Banking Disputes; Sharia Economic Law; Fiqh Muamalah; Religious Court